PENGARUH KEGIATAN REMAJA MASJID, SHOLAT ZHUHUR BERJAMAAH DAN TAHFIDZ ALQURAN TERHADAP KARAKTER RELIGIUS SISWA SMP: The Contribution of Mosque Youth Activities, Congregational Dhuhr Prayer, and Qur’an Memorization to the Religious Character of Junior High School Students - Jaelani, Deny Ahmad; Nurpriatna, Ade; Nurachadijat, Kun (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
This study investigates the contribution of mosque-based youth activities, congregational Dhuhr prayer, and Qur’an memorization (tahfizh) to the development of students’ religious character at SMP Negeri 5 Satu Atap Gegerbitung, Sukabumi Regency, Indonesia. Employing a quantitative approach with a causal-correlational design, the study involved a population of 237 students, from which 70 respondents were selected through proportional sampling techniques. The findings reveal that youth mosque activities do not exhibit a statistically significant contribution to students' religious character (p = 0.123 > 0.05; t = 1.563 < t-table = 1.994). However, congregational Dhuhr prayer and Qur’an memorization were found to significantly contribute to students’ religious character. Specifically, congregational prayer showed a correlation coefficient (r) of 0.652 with a determination coefficient (r²) of 0.425 (42.5%), while Qur’an memorization demonstrated a stronger correlation (r = 0.971) with a determination coefficient (r²) of 0.943 (94.3%). Furthermore, the multiple linear regression analysis confirmed that all independent variables collectively contribute to the religious character of students, yielding a combined correlation coefficient (r) of 0.974 and a coefficient of determination (r²) of 0.949 (94.9%). These findings underscore the significant role of school-based religious practices in shaping students’ moral and spiritual development.